An enhanced house price index model in Malaysia: Maqasid Shariah perspectives - Nik Nor Amalina, Nik Mohd Sukrri (2023)
The house price index (HPI) has become an important tool for measuring housing market performance in Malaysia. Having reviewed the current model of the Malaysian House Price Index (MHPI), it was discovered that HPI is constructed based on demand-driven variables. Previous studies alluded that both macroeconomic and supply factors should be incorporated into the HPI construction to obtain a better reflective indicator. Therefore, this study aims to construct an enhanced HPI model in Malaysia. The time series analysis technique known as the autoregressive distributed lag model (ARDL) was adopted to analyse the short and long-run dynamics between the variables. The existing determinants of HPI were first examined. The data employed in this study was quarterly data from the first quarter of 2008 to the fourth quarter of 2018. The findings revealed that the construction cost and home financing are significant in determining HPI, while the overnight policy rate and land supply are insignificant. Hence, a new enhanced HPI incorporating new demand and supply variables was developed using the Laspeyres approach. The analysis shows that the enhanced HPI has also recorded the same trend but with a lower price value than the current MHPI. This enhanced HPI model is able to contribute a better indication of the real housing market situation in Malaysia, which is more reflective of the macroeconomic fundamentals and housing market variables. The implementation of price benchmarks is another contribution as it is consistent with the goals of Shariah to create justice and fairness in financial transactions and serves as a mechanism to prevent people from facing distress and hardship. This study has an important policy implication for the involved parties to have some policy ramifications to further monitor and take appropriate measures in controlling property prices.